Boarding School Management In The Islamic Integrated Junior High School (SMPIT) Nurul Islam Tengaran Semarang Regency - Susilo, Joko (2012)
The aims of this research are (1) to describe the characteristics of the management of curriculum and learning in SMPIT Nurul Islam Tengaran, (2) to describe the characteristics of the management of the students in the SMPIT Nurul Islam Tengaran, and (3) to describe how the characteristics of the management of the hostel and the nurturing of students in boarding SMPIT Nurul Islam Tengaran. The data of this qualitative descriptive research were collected by in-depth interview, documentation, and observation. The source of the data were teachers, students, and stuffs of that school. Data analysis of this research was done by organizing the data, outlines in units, doing the synthesis, compiling into a pattern, and making inferences. The research results show (1) the management of curriculum and learning uses plus and integrated curriculum. Plus means adding various Islamic activities and paying attention to the kind of intelligence of the students based on the results of test MIR. Student's management is more effective by involving all the citizens of the school with an emphasis on morals and formation of character through the conditioning of the supervision and guidance of all the citizens of the school. (2) The management of the boarding school is efficient and clear when management of the school is separated in dormitory. Management of boarding school aims at improving services to students and is performed by local culture approach and the Islamic leadership principles. (3) The management of the hostel is carried out with full responsibility and compassion so that it can overcome the students difficulties, students learning and task of parenting model, discipline and religion.